(untitled) (Orinoquia, 2023)
By 2050 the global population will reach 9.1 billion, 15 percent higher than 2021 (FAO, 2009). To feed this larger population, annual cereal and meat production will need to rise to 7 and 40%, respectively, above current production levels. Therefore, human food and animal feed production must optimize sustainable practices to ensure cereal and meat animal demands are met while also maintaining natural and environmental resources. As the food demand for humans increases, livestock animals that consume grains including corn, wheat, and soybean are recognized as potential competitors to human food supply and security (Muscat et al., 2020). In this context, feeding strategies that incorporate alternative feedstuffs in livestock diets, such as co-products from agro-industrial crops, will reduce competition for human food ingredients and contribute to sustainable meat animal production. In addition, incorporating alternative ingredients in livestock diets can reduce feed costs and increase profitability, particularly in the swine and poultry industries where the feed costs represent 60 to 70% of the total production cost (Woyengo et al., 2014).